CompTIA Network+ N10-007 : complete video course - Wallace, Kevin, 1965- (LiveLessons (Indianapolis, Ind.), 2018)
17+ Hours of Video InstructionCompTIA Network+ N10-007 Complete Video Course is a comprehensive training course that brings CompTIA Network+ exam topics to life through the use of real-world demonstrations, animations, live instruction, and configurations, making learning these foundational networking topics easy and fun. Best-selling author, expert instructor, and double CCIE Kevin Wallace walks you through the full range of topics on the CompTIA Network+ N10-007 exam, including protocol reference models; network devices, topologies, and services; WAN technologies; network cables and connectors; network design; LAN technologies; network addressing and routing; unified communication; virtualization; network security; and network maintenance. This unique product contains multiple types of video presentations, including live instructor whiteboarding, real-world demonstrations, animations of network activity, dynamic KeyNote presentations, doodle videos, and hands-on router and switch CLI configuration and troubleshooting in real lab environments, enabling you to learn both the concepts and the hands-on application. The 200+ videos contained in this product provide you more than 17 hours of instruction. Modules are divided into easy to digest lessons and conclude with summaries. Designed to take you inside Network+ concepts in a unique and interactive way, CompTIA Network+ N10-007 Complete Video Course is guaranteed to help you master the foundational networking topics that will help you succeed on the exam and on the job. Skill LevelBeginner What You Will Learn Fundamental networking concepts, such as protocol reference models, network devices and theory, network topologies, and network services WAN technologies including ISDN, Frame Relay, PPP, MPLS, Metro-Ethernet, and more How to work with different network cables and connectors Network design considerations Switch and wireless LAN configuration IPv4 and IPv6 addressing Routing fundamentals including RIP, OSPF, IS-IS, and BGP routing protocols; HSRP and VRRP; route aggregation; and routing metrics Unified communications, Voice over IP (VoIP), video, and QoS Virtualized devices, storage area network technologies (SAN), and cloud technologies Network security attacks, vulnerabilities, policies, defenses, and counter-measures Network monitoring tools and analysis, configuration management, and best practices Network troubleshooting Who Should Take This Course?Anyone interested in obtaining their CompTIA Network+ certification or anyone interested in learning basic networking concepts, configuration, and troubleshooting skills. Course RequirementsAlthough this complete video training product does not assume any prior knowledge of network administration or configuration, you should understand the fundamental purposes of a network and be comfortable working with a computer.